Enhancing College Students’ Reading Comprehension Through Critical Reading - Nisa Fitri; Yetti Zainil (Journal of English Language Teaching, 2018)
Reading comprehension is the main pillar during reading activity in order to build the understanding of the text. Improving reading comprehension skills can positively impact many facets of student academic performance. However, it is not an easy activity to do.  Vocabulary limitation and a complex process of reading comprehension lead to students’ failure in reading. This paper discusses how to implement critical reading as one of ways to help students in reading comprehension. Critical reading means that a reader applies certain processes that result in enhanced clarity and comprehension. The process starts from previewing the physical appearance of the text, contextualizing (after reading the whole text), questioning to understand and remember, to answering and evaluating argument. By applying the stages of critical reading, the teacher can facilitate their reading comprehension.